# Tarea 5

Multiplicación de monomios

Ejercicio 38

Multiplicar:
1

(a )(− 3a )(a 2 )

2

(3x )(− x y )(− a x )

3

(− m n)(− 3m )(− 5mn )

4

(4a )(− 5a x )(− ay )

5

(− a )(− 2ab)(− 3a b )

6

 1 3  2 2  3 4 
 x  − a x  − a m 
 2  3
 5

7

 2 m  3 2 4 
4 x
 a  a b  − 3a b
3
4



8

 3 3
 1 x a
2
 − m  − 5a m  − a m 
 5 
 10

9

(2a )(− a 2 )(− 3a 3 )(4a )

10

(− 3b )(− 4a b)(ab)(− 5a x )

11

(a b )(− a )(− 2ab)(− 3a x )

12

 1 2  3 2  10 3  3 2 
 − x y  − xy  − x  − x y 
 2
 5
 3  4

2

3

2

2

2

2

3

3 2

2

m

2 x

(

(

)

2

m x

)

3

2

2

2

RESPUESTAS:
1

(a )(− 3a )(a 2 )
(a )(− 3a )(a 2 ) = 1 ⋅ −3 ⋅1 ⋅ a1+ 2 +1 = −3a 4

2

(3x )(− x y )(− a x )
2

3

2

(3x )(− x y )(− a x ) = 3 ⋅ −1 ⋅ −1 ⋅ a
2

3

3

2

2

⋅ x 2 + 3+1 ⋅ y = 3a 2 x 6 y

(− m n)(− 3m )(− 5mn )
2

2

3

(− m n)(− 3m )(− 5mn ) = −1 ⋅ −3 ⋅ −5 ⋅ m
2

4

2

3

2

3 2

2

= 15m5n 4

2

3 2

2

2 + 3 +1 2

x y 2 = 20a 6 x 2 y 2

(− a )(− 2ab)(− 3a b )
m

2 x

(− a )(− 2ab)(− 3a b ) = −1 ⋅ −2 ⋅ −3 ⋅ a
m

6

n

(4a )(− 5a x )(− ay )
(4a )(− 5a x )(− ay ) = 4 ⋅ −5 ⋅ −1 ⋅ a

5

2 + 2 +1 1+ 3

2 x

m +1+ 2 1+ x

b

= −6a m + 3b x +1

 1 3  2 2  3 4 
 x  − a x  − a m 
 2  3
 5

6 6 4
1
 1 3  2 2  3 4  1⋅ −2 ⋅ −3 2+4 3+1
⋅a x m =
a x m = a 6 x 4m
 x  − a x  − a m  =
2⋅ 3⋅5
30
5
 2  3
 5

7

(

 2 m  3 2 4 
4 x
 a  a b  − 3a b
3
4



)

2 ⋅ 3 ⋅ −3 m + 2 + 4 4 + x
18
3
 2 m  3 2 4 
4 x
a
b = − a m + 6b x + 4 = − a m + 6b x + 4
 a  a b  − 3a b =
3⋅ 4
12
2
 3  4

(

8

(

)

)

 3 3
 1 x a
2
 − m  − 5a m  − a m 
 5 
 10

15
3
 3 3
 1 x a  − 3 ⋅ −5 ⋅ −1 2+ x 3+1+a
2
a m
= − a x + 2 m a+ 4 = − a x + 2 m a + 4
 − m  − 5a m  − a m  =
5 ⋅10
50
10
 5 
 10

(

9

)

(2a )(− a 2 )(− 3a 3 )(4a )
(2a )(− a 2 )(− 3a3 )(4a ) = 2 ⋅ −1 ⋅ −3 ⋅ 4 ⋅ a1+ 2 + 3+1 = 24a7

10

(− 3b )(− 4a b)(ab)(− 5a x )
2

3

2

(− 3b )(− 4a b )(ab )(− 5a x ) = −3 ⋅ −4 ⋅ 1 ⋅ −5 ⋅ a
2

11

3

2

3 +1+ 2 2 +1+1

x = −60a 6b 4 x

(a b )(− a )(− 2ab)(− 3a x )
m x

2

2

(a b )(− a )(− 2ab)(− 3a x ) = 1 ⋅ −1 ⋅ −2 ⋅ −3 ⋅ a
m x

12

b

2

2

m + 2 +1+ 2 x +1

b

x = −6a m + 5b x +1x

 1 2  3 2  10 3  3 2 
 − x y  − xy  − x  − x y 
 2
 5
 3  4

 1 2  3 2  10 3  3 2  − 1 ⋅ −3 ⋅ −10 ⋅ −3 2+1+ 3+ 2 1+ 2 +1 90 8 4 3 8 4
x
y
=
x y = x y
 − x y  − xy  − x  − x y  =
2⋅5⋅3⋅ 4
120
4
 2
 5
 3  4